2011
DOI: 10.1530/rep-10-0485
|View full text |Cite
|
Sign up to set email alerts
|

Oocytes in sheep homozygous for a mutation in bone morphogenetic protein receptor 1B express lower mRNA levels of bone morphogenetic protein 15 but not growth differentiation factor 9

Abstract: The aim of this study was to test the hypothesis that the high ovulation rate in ewes (BB) homozygous for a mutation in the bone morphogenetic protein receptor type 1B (BMPR1B) gene is linked to lower BMP15 and/or GDF9 mRNA in oocytes compared with those in wild-type (CC) ewes. Cumulus cell-oocyte complexes (COC) and granulosa cells (GC) were recovered from R1 mm diameter follicles of BB and CC ewes during a prostaglandin-induced follicular phase. Expression levels of GDF9 and BMP15 were measured by multiplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…A possible mechanism for these interactions was identified when it was shown that BMP15 mRNA levels were decreased in animals carrying the Woodlands gene (Feary et al 2007) or homozygous for the Booroola gene (Crawford et al 2011) compared with their wild-type contemporaries. However, BMP15 mutations have also been observed in flocks carrying other putative major genes influencing ovulation rate wherein the effect is additive rather than synergistic.…”
Section: R113mentioning
confidence: 99%
See 2 more Smart Citations
“…A possible mechanism for these interactions was identified when it was shown that BMP15 mRNA levels were decreased in animals carrying the Woodlands gene (Feary et al 2007) or homozygous for the Booroola gene (Crawford et al 2011) compared with their wild-type contemporaries. However, BMP15 mutations have also been observed in flocks carrying other putative major genes influencing ovulation rate wherein the effect is additive rather than synergistic.…”
Section: R113mentioning
confidence: 99%
“…The follicle therefore develops characteristics of an ovulatory follicle at a smaller size. This can be demonstrated through the increased proportions of smaller diameter follicles in Booroola and Inverdale animals with granulosa cells capable of responding to LH in vitro , Crawford et al 2011. Originally, granulosa cells from Booroola and Inverdale animals were thought to have an increased responsiveness to FSH, but it has been shown recently that this is not the case.…”
Section: Mechanisms Of Action Of Gdf9 and Bmp15 And The Involvement Omentioning
confidence: 99%
See 1 more Smart Citation
“…54,57 The latter finding is due to significant interactive effects of follicular diameter and genotype where the GC populations were often lower in follicles 1.0 mm in I+ ewes than in ++ ewes. 53 Moreover, from detailed analyses of individual follicles, the higher ovulation rate in I+ ewes was due to a greater proportion of follicles acquiring LH-responsive GC at smaller diameters, compared to that in ++ animals. 57 Thus, the ovulation rate in I+ ewes occurs because follicles of different diameters respond to LH and ovulate with a total number of GC, and subsequent CL cells, that are not different from that in ++ animals.…”
mentioning
confidence: 97%
“…52 It's also noteworthy that the ALK6-mutant sheep express lower levels of BMP15 mRNA. 53 Evidence that a partial reduction in BMP15 or GDF9 bioactivity is directly responsible for the significant increases in ovulation rate was demonstrated by immuno-neutralization experiments 12 : the increase was due to significantly more animals having two or more ovulations. In a large follow-up study involving more than 400 ewes, BMP15 immuno-neutralization significantly increased pregnancyrates without affecting embryo or fetal survival.…”
mentioning
confidence: 99%